Modified traditional Chinese medicine formula: is it still effective? - Siat Yee Fong (Penerbit UMS, 2022)
Traditional Chinese medicine (TCM) is a medical system recorded over 2,000 years ago and it is making a comeback in the 21st century. Basic theories of TCM are based on the Chinese philosophy of Yin-Yang, Qi and the Five Elements (Ma et al., 2021). In TCM, balance and harmony with the environment (nature) are keys to good health and imbalances will lead to illnesses (Cheung et al., 2020). One of the approaches used by TCM practitioners to treat illnesses is the use of natural medicine derived from plants and animals (Ma et al., 2021). In practice, a combination of two or more medicinal materials (known as TCM formulas), having synergistic effects, is often used to achieve optimal therapeutic efficacy, while attenuating toxicity (Zhang et al., 2017). However, some of the materials derived from animal and plant species, such as the rhinoceros (Rhinocerotidae), tiger (Panthera tigris) and caterpillar fungus (Ophiocordyceps sinensis), which are traditionally used, are now endangered (Cheung et al., 2020). Besides, the distribution of some plant species and substances derived from these species, including Ephedra spp. (Ma Huang), Aconitum spp. (Fu Zi and Chuan Wu) and Aristolochia spp. (Mu Tong and Fang Ji) are restricted or banned in some countries due to their toxicity (Fleischer et al., 2017). Therefore, a question arises as to whether the modification of TCM formulas to eliminate these ingredients could affect their therapeutic efficacy.